2020
DOI: 10.1097/shk.0000000000001608
|View full text |Cite
|
Sign up to set email alerts
|

Is Tranexamic Acid Associated With Mortality or Multiple Organ Failure Following Severe Injury?

Abstract: Background: Tranexamic acid (TXA) administration is recommended in severely injured trauma patients. We examined TXA administration, admission fibrinolysis phenotypes, and clinical outcomes following traumatic injury and hypothesized that TXA was associated with increased multiple organ failure (MOF). Methods: Two-year, single-center, retrospective investigation. Inclusion criteria were age 18 years, Injury Severity Score (ISS) >16, admitted from scene of injury, thromboelastography within 30 min of arrival. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Our data are in line with several other reports in the literature suggesting that TXA in a polytrauma population was not associated with increased TEC and mortality even if it was administered liberally [10][11][12][13]. However, current data are in contrast to other studies that demonstrated increased mortality after TXA [6][7][8][9]. A possible explanation for these seemingly contradicting data was proposed by Moore et al suggesting that outcome after TXA might be related to fibrinolytic state of the patient with least expected benefit from TXA in patients with physiological fibrinolysis [9,24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data are in line with several other reports in the literature suggesting that TXA in a polytrauma population was not associated with increased TEC and mortality even if it was administered liberally [10][11][12][13]. However, current data are in contrast to other studies that demonstrated increased mortality after TXA [6][7][8][9]. A possible explanation for these seemingly contradicting data was proposed by Moore et al suggesting that outcome after TXA might be related to fibrinolytic state of the patient with least expected benefit from TXA in patients with physiological fibrinolysis [9,24].…”
Section: Discussionsupporting
confidence: 90%
“…These results have led to widespread incorporation of TXA in damage control resuscitation with low thresholds to administer TXA, including in prehospital settings. However, concerns have been raised that indiscriminate widespread adoption might result in TXA administration in the wrong patients, leading to increased morbidity and mortality [6][7][8][9]. Data in the literature have been contradicting, however, with others reporting no significant differences or even decreased adverse effects [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Walker and colleagues 33 demonstrated that TXA reduced inflammation in the lung but at the same time caused myocardial injury in a rodent model. In addition several clinical studies have suggested TXA may lead to worse outcomes in different trauma populations based on coagulation phenotype as determined by TEG 34–36 . In our study, TXA at concentrations with limited anti-fibrinolytic activity led to equivalent protection from HR and epi effects on the endothelial glycocalyx vascular barrier.…”
Section: Discussionsupporting
confidence: 59%
“…12 Some studies support treating hyperfibrinolytic states with antifibrinolytics (e.g., tranexamic acid), [14][15][16][17] although concerns have been raised regarding the potential that administering tranexamic acid to patients with shutdown may enhance risk of thromboembolic complications. [18][19][20] Characterizing mechanisms driving fibrinolytic phenotypes is important for defining the underlying etiology and improving trauma-related treatment and outcomes.…”
mentioning
confidence: 99%